ANALISIS PEMBALIKAN ARUS MODAL GLOBAL SECARA MENDADAK (SUDDEN REVERSAL): STUDI KASUS KOREA DAN INDONESIA - Widita Kurniasari (MediaTrend, 2010)
The aim of this paper is to explain sudden reversal of flow in global capital. This paper uses the general capital mobility model as its main analysis tool. In addition Korea and Indonesia is choosen as the country case study. Furthermore, the study finds that both countries, Indonesia and Korea, are very vulnerable to the possibility of 'sudden reversal' of capital flow. Whilst the huge amount of short term debt is the main causes of 'sudden reversal' in Korea, the huge amount of foreign ownership in local assets is the main cause for Indonesia.